Pengaruh Financial Knowledge, Income, dan Financial Attitude Terhadap Pengelolaan Keuangan Pada Masa Pandemi Covid-19 - Ari Sulistyowati; Kiky Ayuning Pratiwi (Jurnal Ilmiah Akuntansi dan Manajemen, 2022)
The Influence of Financial Knowledge, Income, and Financial Attitude on Financial Management During the COVID-19 Pandemic. This study is a study used to measure the effect of financial knowledge, income, and financial attitude on financial management during the COVID-19 pandemic. This study is a quantitative study where the object used is the 2017 class of students, Faculty of Economics and Business, Bhayangkara Jakarta Raya University. This research was conducted by non-probability sampling with purposive sampling method. The number of samples used in this study were 192 respondents. The design used in this study is hypotesis testing using the Structural Equitation Model (SEM) – SmartPLS 3.0. The result of this study provide an explanation that the variables of financial knowledge, income, and financial attitude have a positive and significant effect on financial management. This study has a limited object of research which was only conducted on students of the 2017 class of the Faculty of Economics and Business, Bhayangkara Jakarta Raya University. This can be a suggestion for further researchers. The novelty in this study combines the variables of financial knowledge, income, and financial attitude towards financial management in a research model conducted on students of Bhayangkara Jakarta Raya University.